Granular Cell Tumors of Breast – 2 Case Reports - Shuba C; Hareesh Chandran; Deepthi Mishra; Aruna Prabhu; Karthick Rajamanickam (Annals of Pathology and Laboratory Medicine, 2026)
Introduction: Granular cell tumors are mostly benign soft tissue tumors said to show neuroectodermal differentiation and originate from Schwann cells. These tumours most commonly occur in females, between ages 40–60 years. They are seen at various sites of the body. They are usually found in the oral cavity (40%), skin and subcutaneous tissue (30%), breast (15%) and respiratory tract (15%). The tumour cells are epithelioid cells with abundant lysosome rich granular cytoplasm and hence stain positive for S100 and CD68. Case Presentation: We had 2 patients who were post menopausal women presenting with breast masses which were clinically suspicious, radiologically was in close relation to muscle and were suggested excision biopsy to exclude malignancy. Both breast tumors were evaluated by ultrasonogram, mammography and MRI, showed breast masses with no conclusive benign or malignant features making pathological assessment essential for definitive diagnosis. We evaluated microscopically, which suggested a benign granular cell tumour according to Fanburg Smith criteria and utilized immunohistochemical markers S100, Inhibin alpha and CD68 to reach a confirmatory diagnosis.Conclusion: Breast masses with suspicious radiological features and close relation to muscle require biopsy and immunohistochemistry to ascertain the diagnosis of granular cell tumour.